Energy Management Program Leads to Operational Improvements. Issue 5 (6th May 2019) - Sowby, Robert B.; Jones, Steven C.; Christiansen, Sam; Jensen, Matt
Abstract : The city of North Salt Lake, Utah, recently reduced its water system's energy use by 25 percent. Distribution system pressures and water quality also improved as the water system staff embraced energy‐efficient operations.